Erratum to: Carpal Coalition: A Review of Current Knowledge and Report of a Single Institution's Experience with Asymptomatic Intercarpal Fusion. (June 2013) - DeFazio, Michael V.; Cousins, Benjamin J.; Miki, Roberto Augusto; Cardoso, Roy
The name of one of the authors, Roberto Augusto Miki Jr., was misspelled. We regret the error. The online version of the original article can be found athttp://dx.doi.org/10.1007/s11552-013-9498-5 .